Kajian Teknis dan Analisis Ekonomis PLTS Off-grid Solar System sebagai Sumber Energi Alternatif (Studi Kasus : Dusun Sedayu Desa Pulau Limbung Kecamatan Sungai Raya Kabupaten Kubu Raya ) - kardi, Rus (ELKHA : Jurnal Teknik Elektro, 2015)
Abstract– In this study, the off-grid solar system is used to support the lighting for the residents in Dusun Sedayu. Each house had a total lighting power of 12 Watt consisting of two lamps of 5 Watt and 7 Watt lamp respectively. The technical analysis conducted includes several supporting components such as: the examination of solar panel capacity of 700 WP, the examination of the used battery capacity of 500 Ah, the examination of the BCU capacity of 60 Ampere and the election of the inverter of 12VDC / 220VAC 500 Watt. The results of the economical assessment obtained of the system are as follow: daily average power (P) which can be raised for 10 hours (07.00 am to 17.00 pm) is equal to 337.96 Watt, the average energy per day (Eh) is about 3,3796 kWh, the energy price per unit from the  off-grid solar system is about Rp.13.294,46, - / kWh, and the period of return on investment (payback period) of the off-grid solar energy system is about 4.01 years. By analyzing the Internal Rate Of Return (IRR) of the off-grid solar system, it can be concluded some of the following: IRR with energy prices of Rp.415, - (TDL. PLN) is smaller than the MARR, therefore, the project is stated as infeasible. However, the IRR with energy prices of Rp. 13294.46, - (price per unit of energy) is greater than the MARR, thus, it can be claimed that this project is worth to be done.   Keywords– off-grid, energy, technical,economic, investment.